Identifying the main determinants of part-time employment in EU Countries - Rasa Miežienė; Sandra Krutulienė; Boguslavas Gruževskis (Review of Economic Perspectives, 2021)
The article analyses the prevalence of part-time employment in different EU countries with a focus on the factors affecting the rate of part-time employment across the EU. Based on the literature review, a distinction is made between three groups of factors that are relevant for the rate of part-time employment, in particular, cyclical factors, political and institutional factors, and structural factors. The article analyses how these factors influence part-time employment rates in EU countries. The linear regression analysis based on EU-28 macroeconomic data for the period of 2007-2018 has shown that all three groups of determinants (i.e. cyclical, political and institutional as well as structural factors) affect the rate of part-time employment in the EU-28. Part-time employment is a complex phenomenon which depends on a number of factors. However, the regression analysis has found that the following political and institutional as well as structural independent variables are also significant predictors of part-time employment rates in EU Member States (EU-28): average annual wages, the tax rate on low wage earners, expenditures on children and family benefits as a percentage of gross domestic product, trade union density, and the activity rate of people aged 15-24 and 55-64. Cyclical factors (the unemployment rate in Model (1) and real GDP per capita in Model (2)) have also been found to have a significant effect on part-time employment in EU-28 countries.
Keywords: J22; J81; 330; part-time employment; part-time work; cyclical factors; political and institutional factors; structural factors